Maize-based systems as affected by forage grass and nitrogen fertilization: elucidating 15N recovery, greenhouse gas emissions, N-cycle functional genes in soil and crop yields - Grassmann, Camila da Silva [UNESP] (2021)
Due to the interest in N use efficiency (NUE) and sustainable agricultural systems, the adoption of integrated systems, such as the intercropping of maize with forage grasses can be of great relevance, allowing the use of the land throughout the year, besides avoiding losses of N through nitrate (NO3 - ) leaching, nitrous oxide (N2O) emissions, ammonia volatilization (NH3), and immobilization. Tropical forage grasses of the genus Megathyrsus and Urochloa can suppress soil–nitrification by releasing inhibitory substances, reducing N losses and increasing fertilizer N recovery of the cash crop in rotation. In this way, understanding the N transformations in the soil by microorganisms and the fertilizer recovery in the system are very important. Firstly, the first two chapters are about a 3-year (2014-2017) field experiment conducted in southeastern Brazil, were forage grasses Guinea grass (Megathyrsus maximus cv. Tanzânia), palisade grass (Urochloa brizantha cv. Marandu), and ruzigrass (Urochloa ruziziensis cv. Comum) were cultivated in rotation with maize for grain in summer, to analyze the influence of forage grass and N fertilization in each study. In first chapter, maize was fertilized with 140 kg ha-1 N as (15NH4)2SO4 or not fertilized, and recovery of residual 15N was quantified in the second season. In second chapter, the change was that the N source used was ammonium sulphate not labeled, and were analyzed nitrous oxide (N2O), methane (CH4), and NH3 emissions from the system. In the third and fourth chapter, maize was intercropped with the same grasses previously mentioned. The N rates were 90, 180 and 270 kg ha-1 N and treatments without N fertilization. The objective was also to ascertain the effect of grasses and N fertilization from the analyzes carried out. The third chapter characterized the changes in N-cycle genes in the soil and measured the N2O emissions. The fourth chapter assessed maize grain yield and forage production, bromatological quality, and estimated meat production. In the first season after 15N application, 21%, 65%, and 33% of the N in maize grain, stover, and shoots, respectively, was derived from fertilizer. In the next season, of the total N found in maize grain, stover, and shoots, 2.2%, 1.9%, and 2.0%, respectively, was derived from the residual fertilizer applied in the previous year. There were no differences between forage grass species in the amount of 15N recovered by maize, soil, and total N. In the first season of maize in rotation with forage grasses, Guinea grass, palisade grass, ruzigrass did not affect N2O and NH3 emission due to their apparent inability to suppress soil nitrification. However, N fertilization slightly increases cumulative N2O emission. In maize intercropping with grasses, N fertilization increases the abundance of AOB (amoA of bacteria) more than AOA (amoA of archaea). N2O emission was influenced by AOB, water-filled pore space (WFPS) and N fertilization. Nitrogen fertilization positively affects forage growth and nutritional quality, resulting in a higher maize grain yield, higher forage production and quality, and eventually higher estimated meat production. Moreover, Guinea grass resulted in the highest estimated meat production when fertilized with 270 kg ha-1 N. However, no evidence of biological inhibition by the grasses were confirmed.